The Influence of the Ctl Model Using Amba's Mpa'a Strategy On Improving Students' Speaking Abilities and Local Cultural Literacy - Yani, Muhammad; Wardatunnissa, Yeni; Sarfiah, Sarfiah; Yunita, Yunita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study uses a quantitative approach with a quasi-experimental design model, Pretest-posttest control group design. It was conducted with eighth-grade students at SMPN 1 Ambalawi, with 25 students in the experimental class and 26 students in the control class. The research instruments included a Speaking Test, Local Culture Literacy Test, Observation Sheet, and Interview Questionnaire. The data were analyzed from the Speaking, Local Culture Literacy, and Observation assessments. The validation results indicate that the learning materials and evaluation instruments meet the required standards and are recommended for implementation. The integration of local culture into the learning process received high appreciation, indicating that the culturally-based approach is highly effective in improving students' skills. This study suggests that the use of CTL with the Mpa’a Amba strategy is effective in improving students' English speaking skills, although local culture literacy still requires more time and effort to be fully understood and applied.